2015
DOI: 10.3109/10826084.2015.1073320
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends and Policy Gaps: The Case of Alcohol Misuse Among Adolescents in Lebanon

Abstract: Background-Monitoring studies are crucial for informing and reforming local policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…Our results showed that the prevalence of AUD risk among Lebanese adolescents was 28.0%, in line with other studies 25,75,76 . Besides the correlations with the psychological factors identified in this research, this proportion may also be related to the normalization of alcohol use, its broad availability, particularly in Beirut and Mount Lebanon, the inaction of the government, in addition to existing indefinite policies regarding the illegal sale of alcohol to minors, low excise taxes on alcohol, poor regulatory framework for alcohol advertising and promotion, lack of effectively reported adverse effects of alcohol consumption, and the impact of friends and cousins on the young population 23 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results showed that the prevalence of AUD risk among Lebanese adolescents was 28.0%, in line with other studies 25,75,76 . Besides the correlations with the psychological factors identified in this research, this proportion may also be related to the normalization of alcohol use, its broad availability, particularly in Beirut and Mount Lebanon, the inaction of the government, in addition to existing indefinite policies regarding the illegal sale of alcohol to minors, low excise taxes on alcohol, poor regulatory framework for alcohol advertising and promotion, lack of effectively reported adverse effects of alcohol consumption, and the impact of friends and cousins on the young population 23 .…”
Section: Discussionsupporting
confidence: 93%
“…Due to the immense gaps in the laws and their implementation in Lebanon, there is an urgent need to define new and updated approaches to protect the youth, by raising awareness, setting a legal minimum drinking age 116 , and enforcing the laws 24 . Thus, an evidence-based national alcohol harm reduction plan is warranted 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations